Ostreopsis blooms promote production of volatile organic sulfur compounds: environmental and health implications - Sarah Sadorge; Marie Morère; Cécile Jauzein; Eva Ternon; Mathilde Monperrus (Environmental Pollution, 2026)

Meso- and microplastics accumulate and transfer hazardous contaminants from wastewater treatment plants to the environment - Simone Cavazzoli; Marie Morere; Gianni Andreottola; Mathilde Monperrus (Environmental Research, 2026)

Unravelling the metabolomic signatures of migrant and non-migrant glass eels (Anguilla anguilla) and their response to diazepam exposure - Iker Alvarez-Mora; Valérie Bolliet; Naroa Lopez-Herguedas; Colin Bouchard; Mathilde Monperrus; Nestor Etxebarria (Marine Environmental Research, 2024)

Analysis of micro- and nanoplastics in wastewater treatment plants: key steps and environmental risk considerations - Simone Cavazzoli; Roberta Ferrentino; Costanza Scopetani; Mathilde Monperrus; Gianni Andreottola (Environmental Monitoring and Assessment, 2023)
The analysis of micro- and nanoplastics (MNPs) in the environment is a critical objective due to their ubiquitous presence in natural habitats, as well as their occurrence in various food, beverage, and organism matrices. MNPs pose significant concerns due to their direct toxicological effects and their potential to serve as carriers for hazardous organic/inorganic contaminants and pathogens, thereby posing risks to both human health and ecosystem integrity. Understanding the fate of MNPs within wastewater treatment plants (WWTPs) holds paramount importance, as these facilities can be significant sources of MNP emissions. Additionally, during wastewater purification processes, MNPs can accumulate contaminants and pathogens, potentially transferring them into receiving water bodies. Hence, establishing a robust analytical framework encompassing sampling, extraction, and instrumental analysis is indispensable for monitoring MNP pollution and assessing associated risks. This comprehensive review critically evaluates the strengths and limitations of commonly employed methods for studying MNPs in wastewater, sludge, and analogous environmental samples. Furthermore, this paper proposes potential solutions to address identified methodological shortcomings. Lastly, a dedicated section investigates the association of plastic particles with chemicals and pathogens, alongside the analytical techniques employed to study such interactions. The insights generated from this work can be valuable reference material for both the scientific research community and environmental monitoring and management authorities. Graphical Abstract

Metabolomics to study the sublethal effects of diazepam and irbesartan on glass eels (Anguilla anguilla) - Iker Alvarez-Mora; Valérie Bolliet; Naroa Lopez-Herguedas; Maitane Olivares; Mathilde Monperrus; Nestor Etxebarria (Aquatic Toxicology, 2023)

Keystone microbial taxa organize micropollutant-related modules shaping the microbial community structure in estuarine sediments - Sandrine Veloso; David Amouroux; Laurent Lanceleur; Christine Cagnon; Mathilde Monperrus; Jonathan Deborde; Cristiana Cravo Laureau; Robert Duran (Journal of Hazardous Materials, 2023)

Effect of exogenous and endogenous sulfide on the production and the export of methylmercury by sulfate-reducing bacteria - Sophie Barrouilhet; Mathilde Monperrus; Emmanuel Tessier; Bahia Khalfaoui-Hassani; Rémy Guyoneaud; Marie-Pierre Isaure; Marisol Goñi-Urriza (Environmental Science and Pollution Research, 2023)

Determination of Synthetic Musks in Surface Sediment from the Bizerte Lagoon by QuEChERS Extraction Followed by GC-MS - Mouna Necibi; Laurent Lanceleur; Nadia Mzoughi; Mathilde Monperrus (Bulletin of Environmental Contamination and Toxicology, 2016)

Validation of an Adapted QuEChERS Method for the Simultaneous Analysis of Polycyclic Aromatic Hydrocarbons, Polychlorinated Biphenyls and Organochlorine Pesticides in Sediment by Gas Chromatography–Mass Spectrometry - Fida Ben Salem; Olfa Ben Said; Robert Duran; Mathilde Monperrus (Bulletin of Environmental Contamination and Toxicology, 2016)

Pesticides in Ichkeul Lake–Bizerta Lagoon Watershed in Tunisia: use, occurrence, and effects on bacteria and free-living marine nematodes - Fida Ben Salem; Olfa Ben Said; Patricia Aissa; Ezzeddine Mahmoudi; Mathilde Monperrus; Olivier Grunberger; Robert Duran (Environmental Science and Pollution Research, 2016)

Relationships between bacterial energetic metabolism, mercury methylation potential, and hgcA/hgcB gene expression in Desulfovibrio dechloroacetivorans BerOc1 - Marisol Goñi-Urriza; Yannick Corsellis; Laurent Lanceleur; Emmanuel Tessier; Jérôme Gury; Mathilde Monperrus; Rémy Guyoneaud (Environmental Science and Pollution Research, 2015)

Spatial and seasonal variations of methylmercury in European glass eels (Anguilla anguilla) in the Adour estuary (France) and relation to their migratory behaviour - Julie Claveau; Mathilde Monperrus; Marc Jarry; Herve Pinaly; Magalie Baudrimont; Patrice Gonzalez; David Amouroux; Agnès Bardonnet; Valérie Bolliet (Environmental Science and Pollution Research, 2015)

Comparison of Different Air–Water Gas Exchange Models to Determine Gaseous Mercury Evasion from Different European Coastal Lagoons and Estuaries - Abubaker Sharif; Emmanuel Tessier; Sylvain Bouchet; Mathilde Monperrus; Hervé Pinaly; David Amouroux (Water, Air, & Soil Pollution, 2013)

In situ experiments for element species-specific environmental reactivity of tin and mercury compounds using isotopic tracers and multiple linear regression - Pablo Rodriguez-Gonzalez; Sylvain Bouchet; Mathilde Monperrus; Emmanuel Tessier; David Amouroux (Environmental Science and Pollution Research, 2013)

Atmospheric mercury at mediterranean coastal stations - Ingvar Wängberg; John Munthe; David Amouroux; Maria E. Andersson; Vesna Fajon; Romano Ferrara; Katarina Gårdfeldt; Milena Horvat; Yaacov Mamane; Ety Melamed; Mathilde Monperrus; Nives Ogrinc; et al. (Environmental Fluid Mechanics, 2008)